PENGARUH ASIMETRI KONFLIK TUGAS TERHADAP KINERJA DAN PERAN MANAJEMEN KONFLIK KOLABORASI (Kasus pada Organisasi Non Profit) - Dwita Darmawati; Tohir Tohir; Anisa Sri Restanti (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2019)
This study aims to explore the influence of the composition of perceptual task conflicts on group performance in non-profit organizations. In addition, this study also explores the role of moderators of collaborative conflict management on the influence of the composition of perceptual task conflicts on group performance. Data collection is done by questionnaire. Data were analyzed using hierarchical regression analysis. This study involved 232 respondents from 58 teams / working groups from non-profit organizations namely college scouts, libraries, village level government institutions, early childhood education, PKK organizations and dasa wisma. The results of hierarchical regression analysis indicate that the composition of perceptual task conflicts negatively affects group performance. However, there is not enough evidence of the role of collaboration conflict management in with the influence of the composition of the conflict on the task of the group on group performance. Several implications are given based on the results of this study